Effect of reaction media on clay dispersion and mechanical properties in poly(butylene succinate)/organoclay nanocomposites. Issue 4 (3rd February 2015) - Tian, Qin; Qin, Shuhao; Long, Lijuan; Jiang, Yehua; Zhou, Rongfeng; Zhou, Rong; He, Wentao; Xu, Guomin
Abstract : The effect of the reaction media on clay dispersion and mechanical properties in poly(butylene succinate) (PBS, a biodegradable aliphatic thermoplastic polyester)/organoclay nanocomposites was investigated in this article. The results suggested that the most dispersed structures can be observed for organoclay modified in supercritical carbon dioxide (scCO2 ), which was used as solvent in the modification of montmorillonite in this study known for its environmentally benign, inexpensive, and nonflammable solvent, high diffusivity like a gas, near‐zero surface tension, low viscosity and density like a liquid, and high‐solvency power tunable by adjusting pressure and then organoclay modified in ethanol, while the least for organoclay was modified in distilled water. The results also confirmed intercalation‐predominate structures were obtained for nanocomposites of PBS with organoclay modified in ethanol, the mixture of intercalated and exfoliated structures for nanocomposites of PBS with organoclay modified in distilled water, but when clay was modified in scCO2, exfoliation‐predominate structures were observed for the nanocomposites. The storage modulus was significantly enhanced below the glass transition temperature, and the glass transition temperature shifted to a higher temperature compared with pure PBS and the maximum for PBS‐based nanocomposite of pretreated grafted montmorillonite via modification with trihexyltetradecylphosphonium chloride in scCO2 (OGMMTc). The mechanical properties including tensile strength and notched impact strength first decreased and then increased, whereas flexural strength and flexural modulus steadily and nearly linearly increased, maximum for PBS/OGMMTc nanocomposite, owing to the strong interaction between matrix and clay, which ultimately led to better overall dispersion. J. VINYL ADDIT. TECHNOL., 22:423–432, 2016. © 2015 Society of Plastics Engineers